Pseudophillipsia (Carniphillipsia) (Trilobite) from the Permian Jamal Formation, Isfahan, Iran - H. Ameri; M. Yazdi; A. Bahrami (Journal of Sciences, Islamic Republic of Iran)
The aim of this study is to bridge a gap in the existence of Trilobites in the marine Permian successions of Iran by exploring a stratigraphic section of the Permian in Jamal Formation (Dizlu section).  Based on comprehensive field studies and laboratory investigations three Trilobite specimens were identified in the study area including Pseudophillipsia (Carniphillipsia) dizluensis sp. nov., Pseudophillipsia (Carniphillipsia) sagittalis and Pseudophillipsia (Carniphillipsia) sp.. A new occurrence of trilobites collected from the Permian (Wordian) Jamal Formation at a section at Dizlu, Isfahan Province, Iran, is documented.   They belong to a new species of Pseudophillipsia (Carniphillipsia), which is described herein, and can be attributed to the a group of species centered on P.(C). paffenholzi (Weber). It is based on 30 specimens from a single horizon, most of which are enrolled. Co-occurrence of Pseudophillipsia (Carniphillipsia) sp. A. and stenohalin groups such as brachiopods, bryozoans, and crinoids are indicating that this species were preferred shallow and carbonate environments. This is the first time that the existences of these specimens are reported in Dizlu section.